2011
DOI: 10.2478/v10036-011-0001-5
|View full text |Cite
|
Sign up to set email alerts
|

Is Body Fat a Predictor Variable for Race Performance in Recreational Female Ironman Triathletes?

Abstract: Introduction and aim of the study: Low body fat is related to race performance in endurance athletes. We investigated whether characteristics of anthropometry, training or previous performance were related to race time in recreational female Ironman triathletes.Methods: In 31 female Ironman triathletes, with (mean and SD) 36.8 (6.2) years, 60.8 (6.2) kg body mass, 1.66 (0.06) m body height and a body mass index of 21.6 (1.3) kg/m 2 , anthropometric characteristics, such as body mass, body height, body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In a small sample of recreational female triathletes, personal best time in a marathon ( r = 0.51), personal best time in an Olympic distance triathlon ( r = 0.70), and personal best time in an Ironman triathlon ( r = 0.70) were significantly and positively related to Ironman race time. Also, personal best time in an Olympic distance triathlon was significantly and positively related to personal best time in an Ironman triathlon ( r = 0.63) 29. Personal best times in both an Olympic distance triathlon and a marathon might also be strong and independent predictor variables for Ironman race time in female triathletes, as has been shown here for male athletes.…”
Section: Discussionsupporting
confidence: 75%
“…In a small sample of recreational female triathletes, personal best time in a marathon ( r = 0.51), personal best time in an Olympic distance triathlon ( r = 0.70), and personal best time in an Ironman triathlon ( r = 0.70) were significantly and positively related to Ironman race time. Also, personal best time in an Olympic distance triathlon was significantly and positively related to personal best time in an Ironman triathlon ( r = 0.63) 29. Personal best times in both an Olympic distance triathlon and a marathon might also be strong and independent predictor variables for Ironman race time in female triathletes, as has been shown here for male athletes.…”
Section: Discussionsupporting
confidence: 75%
“…Men have larger skeletal muscle mass [24], correlating with greater muscular strength [16], larger aerobic capacity [17], and lower relative body fatness [25-27] compared to women. Low body fat is an important predictor variable for overall race time in an Ironman triathlon [28].…”
Section: Discussionmentioning
confidence: 99%
“…Low body fat is an important predictor variable for overall race time in an Ironman triathlon [28]. Low body fat was associated with faster race times in male Ironman triathletes [28], while in female triathletes, anthropometric characteristics such as body fat seemed not to be related to Ironman race time [25,27]. However, women retain 7%–9% more percent body fat compared to men [25,26], which is likely to be an advantage for men.…”
Section: Discussionmentioning
confidence: 99%
“…The personal best time in a marathon seems to be a strong predictor variable for female Ironman race time (24,34) and this finding raises the question whether female Ironman triathletes are similar to female marathoners. Since characteristics of both anthropometry and training were related in both marathoners and Ironman triathletes to their specific races times, we intended to investigate whether recreational female marathoners and recreational female Ironman triathletes were similar regarding anthropometry and training.…”
Section: Introductionmentioning
confidence: 95%
“…Leake and Carter (26) reported that training parameters were more important than anthropometric measurements in the prediction of performance for 16 female triathletes. In studies investigating small samples of recreational female Ironman triathletes, weekly training hours (21,22), personal best times in an Ironman triathlon (21,24), personal best time in a marathon (24,34), and personal best time in an Olympic distance triathlon (24,34) were related to an Ironman race time.…”
Section: Introductionmentioning
confidence: 99%